Research on New Words from a Sociolinguistic Point of View (Mongolian Journal of Applied Linguistics, 2024)
New words can only be formed within the framework of a language’s existing vocabulary. The lifespan of new words varies. For example, in the early 1990s, terms like “траншейны хүүхдүүд,” “пейжер,” “уймраа ногоон,” “цэцэг түүх,” “гэзэг сүлжих,” and “ганзагын наймаачин” gradually fell out of use and are no longer in common usage today.These changes in vocabulary are reflected in widely distributed daily newspapers, which cover various genres of writing. From a sociolinguistic perspective, the new vocabulary appearing in these newspapers can be studied to understand the usage and status of new words. This makes newspapers a valuable research tool for examining the enrichment of word meanings and the formation of new words in society.In this context, we created an electronic database containing the vocabulary from newspaper issues sampled from daily newspapers published in Mongolia. Using this database, we calculated the total number of words and their frequency.This article presents the results of research on new words in the state’s discourse from a sociolinguistic perspective. The emergence of new words is important not only for the language but also for understanding societal progress, as well as developments in science and technology.Нийгэм, улс төрийн салбарын үг хэллэгийн давтамж, шинэ үгийг нийгэм хэл шинжлэлийн үүднээс судалсан ньХураангуй: Шинэ үг хэллэг үүсэхдээ тэр хэлнийхээ үгийн сан хөгжин баяжих арга замаас гадуур үүсэх боломжгүй юм. Шинэ үг хэллэгийн шинэ байх хугацаа нь харилцан адилгүй бөгөөд найруулгын төрлүүдээс сонины найруулга нь үгийн сангийн өөрчлөлт хувьслыг өргөнөөр тусгаж байдаг тул өдөр тутмын сонины үгийн санд илэрсэн шинэ үг хэллэгийг нийгэм хэл шинжлэлийн үүднээс судалж, түүний хэрэглээний байдал, шинэ үгийн утгын баяжилт, нийгэмд шинэ үг үүсэх нөхцөл байдлыг судлах нь чухал юм. Иймээс Монгол Улсын өдөр тутмын сонин хэвлэлээс “Өдрийн сонин” сонины 2018.01.03, 2019.01.03, 2020.01.03-ны өдрийн гурван дугаараар цахим сан үүсгэв. Улмаар байгуулсан цахим сандаа тулгуурлан, улс төрийн салбарт үүссэн шинэ үгсийг түүвэрлэн, судалгааны сан бүрдүүлж, шинэ үгийн нийт тоо, давтамжийг тооцоолсны зэрэгцээ, шинэ үг хэллэгийг нийгэм хэл шинжлэлийн үүднээс судалсан судалгааны үр дүнгээ энэхүү өгүүллээр танилцуулахыг зорив. Түлхүүр үг: шинэ үг хэллэг, нийгэм хэл шинжлэл, цахим сан, үгийн давтамж, сонины үг хэллэг.